Evaluation of Female Mayang Club VC 2024 Volleyball Players' Fundamental Underhand Passing Skills - Tarigan, Marsella Br; Tumanggor, Alfredo Zujana; Prastyo, M. Fakhri; Ridho, M.; Hulu, Menwan Putra Jaya; Putri, Cindi Aulia; Winata, Devi Catur (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives: This study aims to assess the proficiency level of basic volleyball underhand passing techniques among female athletes of the Mayang VC club in Simalungun Regency in 2024. Underhand passing is a fundamental technique in volleyball, serving as the primary skill used to receive an opponent's serve. Materials and Methods: This research employs a survey method with a test-based approach. It is a descriptive study designed to evaluate the underhand passing technique proficiency of female athletes at the Mayang VC club. Data were collected through an underhand passing skill test and analyzed descriptively using minimum, maximum, mean, and standard deviation scores. Results: The findings indicate that the minimum score obtained was 3, the maximum score was 9, with an average score (mean) of 6.05 and a standard deviation of 2.06. The distribution of underhand passing skill levels was as follows: very good (1 athlete, 5%), good (10 athletes, 50%), moderate (3 athletes, 15%), poor (4 athletes, 20%), and very poor (2 athletes, 10%). Conclusions: Based on the results, it can be concluded that the overall proficiency level of the basic volleyball underhand passing technique among female athletes of the Mayang VC club in Simalungun Regency in 2024 falls within the